2014
DOI: 10.1084/jem.20131281
|View full text |Cite
|
Sign up to set email alerts
|

IKKβ links vascular inflammation to obesity and atherosclerosis

Abstract: IKKβ functions in smooth muscle cells to regulate vascular inflammatory responses and atherosclerosis development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 75 publications
9
79
0
Order By: Relevance
“…These results are in good agreement with a study by Toure et al (42), who observed reduced neointimal formation in global mDia1 knockout mice. Since SM22α expression has been detected in some myeloid cells (43, 44) and macrophage infiltration has been shown to promote neointima formation, it is difficult to completely eliminate a role for these cells in our model. However, since the majority of neointima cells in our injury model are SMC, we believe that mDia signaling plays a SMC autonomous role in neointimal formation most likely by promoting SMC migration from the medial layer.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in good agreement with a study by Toure et al (42), who observed reduced neointimal formation in global mDia1 knockout mice. Since SM22α expression has been detected in some myeloid cells (43, 44) and macrophage infiltration has been shown to promote neointima formation, it is difficult to completely eliminate a role for these cells in our model. However, since the majority of neointima cells in our injury model are SMC, we believe that mDia signaling plays a SMC autonomous role in neointimal formation most likely by promoting SMC migration from the medial layer.…”
Section: Discussionmentioning
confidence: 99%
“…EMSA was performed as described previously (38,42). Briefly, NPC1L1/DR-4 and CYP3A4/ER-6 probes were created by annealing the oligonucleotides 5Ј-GGGCAGATCACTT-…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%
“…Western blot analysis was performed as previously described (42). Proteins were isolated from cells or mouse tissues by homogenization in RIPA buffer with complete mini protease inhibitor cocktail (Roche).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The systemic inflammation that is associated with atherosclerosis is partly derived from adipose tissue [22,23]. In our previous study we found that hematopoietic C/EBPβ deletion in wildtype mice prevented high fat diet-mediated induction of adipose tissue inflammation [11].…”
Section: Resultsmentioning
confidence: 99%